International tourism carbon footprint and carbon transfer along the belt and road regions - Shi, Hong; Liu, Qijuan; Yan, Ruyu; Li, Taohong; Chen, Ning Chris; Ren, Yun (Frontiers in Environmental Science, 2024)
It is increasingly urgent to constantly monitor and analyze the carbon emission of international tourism activities. This paper focuses on countries and regions along the Belt and Road (B&R), utilizes the MRIO model to approximate international tourism carbon footprint (ITCT), and analyzes the patterns of carbon transfer. Panel model is further applied to discuss the effects of various influencing factors. The results show that: 1) in 2015, ITCT along the B&R accounts for approximately 40.74% of global carbon emission of the year; 2) ITCT along the B&R experienced continuous growth from 2005 to 2015, with an annual growth rate of 3.22%; 3) individual income level, urbanization, and air passenger volume in the countries along the B&R has positive impact on ITCT, which varies according to the income level of the country. The results are of significance for countries and regions along the B&R to formulate future policies for tourism development.